Hypotension and disruption of digestive sutures in critica! irrigation areas. - Esperón, Alejandro; Estellano, Fernando; Salom, Andrés; Aprikián, Darío; Guariglia, Roque; Falconi, Luis (Cirugía del Uruguay, 1988)
Continuing with a previous research, the importance of hypotension due to an intraoperato